2020
DOI: 10.1002/bem.22272
|View full text |Cite
|
Sign up to set email alerts
|

Static Magnetic Field Versus Systemic Calcium Channel Blockade Effect on Microcirculation: Possible Mechanisms and Clinical Implementation

Abstract: The goal was to compare static magnetic field (SMF, generated by Nd 2-Fe 14-B magnets) vasodilator capacity with verapamil (VER, a potent, clinically verified Ca 2+ channel-blocking agent), aimed to assess SMF implementation in conditions with vascular ischemia. Skin microcirculatory blood flow measured by microphotoelectric plethysmogram was recorded in conscious rabbits after 40 min of 0.25 T SMF regional exposure to ear microvascular net (SMF-Vas, n = 20), or 0.35 T to carotid baroreceptors (SMF-Car, n = 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…A significant decrease of the phenylephrine blood pressure ramps after SMF carotid baroreceptor exposure indicates SMF significant baroreceptor stimulatory effect. Carotid baroreceptor magneto‐sensing is a basic physiological mechanism behind the SMF baroreceptor stimulatory effect [Gmitrov, 2020]. SMF induced a notable rise in microvascular dilation in response to i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant decrease of the phenylephrine blood pressure ramps after SMF carotid baroreceptor exposure indicates SMF significant baroreceptor stimulatory effect. Carotid baroreceptor magneto‐sensing is a basic physiological mechanism behind the SMF baroreceptor stimulatory effect [Gmitrov, 2020]. SMF induced a notable rise in microvascular dilation in response to i.v.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that nonuniform, high‐gradient SMF, promoting mechanically and voltage‐gated Ca 2+ influx [Gmitrov and Ohkubo, 2002; Gmitrov, 2020], improves carotid baroreceptor pressure sensitivity and the process of the mechano‐electric signal transduction, which is translated by carotid sinus nerve to the brain autonomic cardiovascular regulation center. Enhanced baroreceptor afferent signaling then transformed into an efferent response consisting of central sympathetic vascular withdrawal, which by impeding arterial smooth muscle L‐type Ca 2+ influx [van Hove et al, 2009; Gamboa et al., 2012], generated increased vessel sensitivity to NO dilatory effect [Gmitrov 2015], improved vessels' compliance and the blood pressure buffering effect.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of human skin blood flow (SBF) when hands or fingers were exposed to a perpendicular SMF have yielded varying results, with SBF reported to decrease [ 51 ], not change [ 52 - 54 ], or show increased vasomotion-related changes [ 55 ]. Other work using SMF on experimental animals has also reported varying results, with SMF exposure causing blood flow to decrease [ 56 , 57 ], not change [ 58 ], increase vascular diameter [ 11 ], and increase or decrease vascular diameter depending on their basal state [ 59 ], and cause alterations in microvascular vasomotion patterns [ 60 , 61 ]. Other aspects of SMF-related impacts on microcirculation in relation to diabetes and wound healing have been presented [ 62 - 64 ].…”
Section: Reviewmentioning
confidence: 99%
“…Static magnetic fields (SMFs), derived either from magnets or from electrical devices carrying non-time-varying currents, are one form of EMFT that has been reported to have a variety of effects, including an increase in microcirculatory blood flow by mediating vasodilation via nitric oxide (NO). Diabetic neuropathy, a major risk factor for diabetic foot ulceration, is associated with impaired blood flow, causing inadequate tissue perfusion and potentially causing ischemia [ 11 ]. Studies have reported that SMF exposure may also have homeostatic, normalizing effects on the vascular tone that may have beneficial effects in situations where tissue perfusion is limited, such as in diabetic neuropathy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation